Biosynthesis of Cucurbita maxima trypsin inhibitor I in the methylotropic yeast Pichia pastoris - Hüsler, Jennifer (Department of Molecular and Cell Biology, 2016)
Squash inhibitors are the smallest natural serine protease inhibitors. Their compact, rigid nature has enabled detailed examination of their 3D structure by NMR and X-ray crystallography. Being of a convenient size to synthesise chemically, the effects on activity of selective substitutions and deletions within the sequence have also been investigated. Thus, this family of inhibitors is considered useful as a model system for the study of protein-protein interactions. Cucurbita maxima trypsin inhibitor I (CMTI I) may be thought of as representative of the squash inhibitors, for which there is detailed structural and functional information available. It is a 29 amino acid protein, with the tri-disulphide bridging pattern common to all squash inhibitors. There are only a few examples of squash inhibitors being produced by recombinant DNA technology. As this technique offers a relatively cheap way of producing large amounts of these proteins, further investigation is required. Problems have been experienced with the expression of disulphide-rich proteins in E. coli, as the cytosol of this microorganism is not conducive to their folding. Furthermore extraction of these proteins from the peri plasmic space is often required, resulting in a reduction in yield. To overcome these shortcomings, the methylotrophic yeast Pichia pastoris was investigated as an alternative means of expression, although at the inception of this work, no disulphide-rich proteins of this size had been expressed in P. pastoris. It was a challenge to investigate the feasibility of producing squash inhibitors in this expression host and to compare the activity of the recombinant inhibitor to that of native CMTI I.